2017
DOI: 10.1634/theoncologist.2016-0488
|View full text |Cite
|
Sign up to set email alerts
|

ALKFusions in a Wide Variety of Tumor Types Respond to Anti-ALK Targeted Therapy

Abstract: Rearrangements involving the gene have been detected in dozens of cancer types using next-generation sequencing. Patients whose tumors harbor rearrangements or fusions respond to treatment with crizotinib and alectinib, including tumors not normally associated with mutations, such as non-Langerhans cell histiocytosis or renal cell carcinoma. Comprehensive genomic profiling using next-generation sequencing can detect targetable fusions irrespective of tumor type or fusions partner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 56 publications
3
99
1
Order By: Relevance
“…ALK rearrangement is often seen in NSCLC (3.1%), whereas its incidence in other tumors is only 0.2% . The data in this study showed that the percentage of Chinese patients with ALK rearrangement was 7.8%, quite high compared with the published data mentioned above.…”
Section: Discussioncontrasting
confidence: 47%
“…ALK rearrangement is often seen in NSCLC (3.1%), whereas its incidence in other tumors is only 0.2% . The data in this study showed that the percentage of Chinese patients with ALK rearrangement was 7.8%, quite high compared with the published data mentioned above.…”
Section: Discussioncontrasting
confidence: 47%
“…NT: mutations were not tested. (2020) 10:2707 | https://doi.org/10.1038/s41598-020-59744-3 www.nature.com/scientificreports www.nature.com/scientificreports/ common mutation sites: EGFR exon 19 deletion (del19) and exon 21 (L858R) 35,36 , KRAS exon 2 (G12C) 37 , BRAF V600E 38 and ALK-EML4 fusion 39 . The frequencies of ALK (5.4%) and ROS1 (2.9%) mutations determined in our study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR del19, EGFR L858R, BRAF V600E, ALK-EML4 and ROS1 fusion mutations in combined (139 cases) accounted for 39.7% of cases in the Vietnamese cohort. They were known as activating mutations and clinically proven to be sensitive to treatments with available TKI drugs 5,6,11,39 . Thus, our findings suggested that approximately 40% of Vietnamese patients would carry such mutations and therefore would benefit from available targeted drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Most ALK-positive NSCLCs result from the juxtaposition of EML4 to ALK and ALK fusions primarily occur at a highly conserved breakpoint in intron 19. 4 In contrast, a multitude of ROS1 breakpoints and fusion partners have been described in ROS1-positive NSCLC. 1,4 Diagnostic approaches that can reliably identify ROS1 fusions are as critical as therapies that selectively and effectively target ROS1.…”
Section: Introductionmentioning
confidence: 99%